Formation and development of the language training methodology for foreign students at classical universities. Part 2. Teaching students of language specialties - N. Ushakova; O. Trostynska; I. Kushnir (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки, 2022)
The article continues the series of scientific and methodological studies on the formation and development of the language training methodology for foreign students at classical universities. In the first part of the research, published last year, the authors analyzed the development of language training conceptual foundations for foreign students of different specialties, as well as history, principles, and features of language education of foreign students of non-philological specialties by the example of the Language Training Department 1 of V.N. Karazin Kharkiv National University. For this group of students, a foreign language is primarily a means of learning and mastering their future specialty. For foreign students of philological specialties, a language is not only a means but also a study goal that involves, besides language proficiency, knowledge of its phonetic, grammatical and lexical structure, mastering various stylistic means, knowledge of modern linguistic concepts, and familiarity with foreign language fiction. The article presents an analysis of the development of scientific and methodological principles for training foreign philological students and illustrates the main directions of their practical implementation by the Language Training Department 1 of the Institute of International Education for Study and Research of V.N. Karazin Kharkiv National University.